Controlled synthesis of silkworm cocoon-like α-Fe2O3 and its adsorptive properties for organic dyes and Cr(VI). (April 2018) - Liu, Hua; Wang, Zumin; Li, Haiyan; Wang, Hao; Yu, Ranbo
Graphical abstract: A hierarchical structured α-Fe2 O3 is synthesized by using a simple hydrothermal method. These α-Fe2 O3 shows high adsorption capacities for CR, MO and Cr(VI) ions with the removal efficiency up to 99.2%, 83.9% and 100% under the given conditions. The synergistic adsorption of organic and inorganic pollutants can be achieved in the solution of mixed CR and Cr(VI) ions. Highlights: A hierarchical structured α-Fe2 O3 is synthesized by using a simple hydrothermal method. The as-synthesized α-Fe2 O3 shows high adsorption capacities for CR, MO and Cr(VI) ions. The removal efficiency can reach up to 99.2%, 83.9% and 100% under the given conditions. This kind of material realizes synergistic adsorption of organic and inorganic pollutants. And the adsorption efficiency can reach 94.7% for CR and 97.9% for Cr(VI) ions in a mixed solution. Abstract: Industrial wastewater containing both organic and inorganic pollutants is being generated all the time. Efficient materials are highly needed to purify the polluted water. Thus, a hierarchical structured α-Fe2 O3 with excellent adsorptive property has been synthesized by using a facile hydrothermal method. It can be prepared in macroscopic quantity. The as-synthesized α-Fe2 O3 with silkworm cocoon-like morphology shows high efficiency in adsorbing Congo red (CR), Methyl orange (MO) and Cr(VI). The removal efficiency of CR, MO and Cr(VI) can reach 99.2%, 83.9% and 100% under appropriate conditions. Besides, this α-Fe2 O3 shows high adsorptive ability for mixed CR and Cr(VI) in aqueous solution and the final removal rates can reach 94.7% and 97.9%, respectively. The adsorption kinetics fits well with the pseudo-second-order kinetic model. The results indicate that the product may find potential application in purification of wastewater containing both organic and inorganic pollutants.